Challenges of Students In Learning The Islamic Yellow Book at Dayah Raudhatul Qur'an Darussalam, Aceh Besar, Indonesia - Fahmi Makraja; Ulil Azmi (DAYAH: Journal of Islamic Education, 2023)
This research discusses the challenges of Dayah Raudhatul Qur'an Darussalam students in learning the yellow book. Dayah Raudhatul Qur'an Darussalam is one of the traditional dayahs in Aceh Besar district that still maintains the concept and learning model of classical "beut seumeubeut". The location of Dayah Raudhatul Qur'an is very strategic, which is located between two well-known campuses in Aceh, namely Syiah Kuala University and Ar-Raniry State Islamic University. The majority of students in Dayah Raudhatul Qur'an Darussalam are students from the two campuses and some from other campuses. This research uses a descriptive qualitative method, with the aim of discussing the challenges of Dayah Raudhatul Qur'an students in learning the yellow book. This research data was obtained through literature studies, observations and interviews. From the collected data, it was analyzed with a descriptive approach, namely describing the yellow book learning system in Dayah Raudhatul Qur'an Darussalam whose students were actually students. The results of this study show that there are several challenges for Dayah Raudhatul Qur'an Darussalam students in learning the yellow book, including lack of teaching staff, lack of learning time, insufficient and irregular repeating time, many student activities, and the negative impact of using technology.